Introduksi Teknologi Budidaya Kacang Hijau di Lahan Sawah Bekas Padi - Purwanto Purwanto; Bambang Rudianto Wijonarko; Tarjoko Tarjoko (Universitas Jenderal Soedirman, 2020)
The current season shift caused the rice planting period in MT II to retreat around May-June this resulted in crop failure due to limited irrigation water only relying on rain. The cropping pattern which was originally rice bero, in several locations in Sumilir Village the planting pattern was only rice in MT 1, while entering MT II who planted rice experienced drought resulting in puso. In an effort to increase cropping in paddy fields after rice, it can be done for the cultivation of green bean palawija plants. Problems that arise include: a. cropping patterns in paddy fields in Sumilir Village are paddy-paddy and paddy-paddy so that paddy fields are still not widely used economically, b. planting green beans on land has never been done in the village of Sumilir, Kec. Kemangkon, c. the unavailability of superior varieties of green beans in the village of Sumilir, and d. Nutrition management of mung bean plants in the former paddy fields has not been mastered. To overcome the problems of partners, several technology solutions offered are technology transfer through mentoring, training and demonstration plots. Evaluation of activities is carried out in the form of monitoring which is carried out after the training, counseling, guiding and demonstration plots are completed. The results of the activity showed that farmers were able to absorb knowledge about the cultivation of green beans in paddy fields properly. The demonstration plot was carried out in the area of paddy fields in Sumilir Village with an area of 1.4 ha. The initial growth of plants showed that plants that were able to grow reached 80 percent. Low yield caused by drought stress since early vegetative phase.